2020
DOI: 10.1021/acs.jafc.0c02161
|View full text |Cite
|
Sign up to set email alerts
|

Serum Protein N-Glycans in Colostrum and Mature Milk of Chinese Mothers

Abstract: To study the Chinese human milk N-glycome over lactation, N-glycans were released and separated from serum proteins, purified by solid-phase extraction, and analyzed by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS). In total, 66 different putative N-glycans were found in the colostrum (week 1) and mature milk (week 4) of seven Chinese mothers. A clear difference was observed between milk of five secretor and two nonsecretor mothers, based on the type and relative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
2
6
1
Order By: Relevance
“…As shown in Table S4, 23 N -glycans all share a common core sequence, Manα1–3­(Manα1–6)­Manβ1–4GlcNAcβ1–4GlcNAcβ1-Asn-X-Ser/Thr, and could be classified into three types: oligomannose, in which only Man residues extend the core (H5N2, H6N2); complex, in which “antennae” initiated by GlcNAc extend the core (H3N4, H3N5, H5N4-1/3, H3N5F1, H5N4F1-1/2/3, H5N4F1A1-1/2); hybrid, in which one branch of the core was extended by Man and another was extended by one or two GlcNAcs (H3N3F1, H4N3-1/2, H4N3F1-1/2/3, H4N3A1, H5N4-2, H4N3F1A1-1/2/3) . Besides, it was found that the amount of neutral N -glycans (17) in human milk was greater than that of acidic N -glycans (6); similarly, the amount of fucosylated N -glycans (9) in human milk exceeded that of sialylated N -glycans (6), consistent with previous studies. ,, The extracted ion chromatogram and the peak area of each N -glycan derivative are shown in Figure S2 and Table S4, respectively, and the peak area was used for quantitative comparison. The level of total N -glycans was highest at day 7 and fell abruptly at day 15 and month 1, which is consistent with the findings of Bai et al The content of N -glycans at day 15 was similar to that at month 1, month 7, and month 8, which were less than that at month 2 to month 6 (Figure ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As shown in Table S4, 23 N -glycans all share a common core sequence, Manα1–3­(Manα1–6)­Manβ1–4GlcNAcβ1–4GlcNAcβ1-Asn-X-Ser/Thr, and could be classified into three types: oligomannose, in which only Man residues extend the core (H5N2, H6N2); complex, in which “antennae” initiated by GlcNAc extend the core (H3N4, H3N5, H5N4-1/3, H3N5F1, H5N4F1-1/2/3, H5N4F1A1-1/2); hybrid, in which one branch of the core was extended by Man and another was extended by one or two GlcNAcs (H3N3F1, H4N3-1/2, H4N3F1-1/2/3, H4N3A1, H5N4-2, H4N3F1A1-1/2/3) . Besides, it was found that the amount of neutral N -glycans (17) in human milk was greater than that of acidic N -glycans (6); similarly, the amount of fucosylated N -glycans (9) in human milk exceeded that of sialylated N -glycans (6), consistent with previous studies. ,, The extracted ion chromatogram and the peak area of each N -glycan derivative are shown in Figure S2 and Table S4, respectively, and the peak area was used for quantitative comparison. The level of total N -glycans was highest at day 7 and fell abruptly at day 15 and month 1, which is consistent with the findings of Bai et al The content of N -glycans at day 15 was similar to that at month 1, month 7, and month 8, which were less than that at month 2 to month 6 (Figure ).…”
Section: Resultssupporting
confidence: 84%
“…57 Besides, it was found that the amount of neutral Nglycans (17) in human milk was greater than that of acidic Nglycans (6); similarly, the amount of fucosylated N-glycans (9) in human milk exceeded that of sialylated N-glycans (6), consistent with previous studies. 32,37,58 The extracted ion chromatogram and the peak area of each N-glycan derivative are shown in Figure S2 and Table S4, respectively, and the peak area was used for quantitative comparison. The level of total N-glycans was highest at day 7 and fell abruptly at day 15 and month 1, which is consistent with the findings of Bai et al 31 The content of N-glycans at day 15 was similar to that at month 1, month 7, and month 8, which were less than that at month 2 to month 6 (Figure 4).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Yang et al 23 applied a similar method to compare N-glycosylation in milk fat globule membranes across species, and found that N-glycoproteins in humans were less similar to each other than those in other species. Elwakiel et al 26 used MALDI-TOF-MS to analyze the N-glycans enzymatically released from the glycoproteins in colostrum and mature milk from seven Chinese mothers and identified 66 N-glycans in colostrum and mature milk from seven Chinese mothers. It should be noted that the analysis of the deglycosylated peptides or released glycans cannot reveal the glycoform variation on particular glycosites.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides the distinct amount and composition of proteins and endogenous peptides in preterm milk, significant technological advances have been achieved concerning posttranslational modifications (PTMs) [56]. PTMs are vital to protein structure, stability, function, and health of the intestinal mucosa [57], which might be critical for the usage and effects of proteins and peptides ingested by preterm infants.…”
Section: Current Practices and The Gap In Infant Needsmentioning
confidence: 99%